Analisis Realisasi Anggaran Belanja Pada Badan Perencanaan Pembangunan Daerah Provinsi Sumatera Utara - Nadila Silvi Amanda; Muhammad Ihsan Harahap (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
This research is entitled "Analysis of Budget Realization at the Regional Development Planning Agency of North Sumatra Province". The purpose of this research is to find out which budget items are less efficient from 2018-2020 at the Regional Development Planning Agency of North Sumatra Province. The types of data used are primary data and secondary data. The method used is the descriptive-explanation method. Data collection techniques used are interview and documentation techniques. The results of the study show that the budget items that are less efficient starting from 2018-2020 are personnel expenditures, capital expenditures for machine and machine tools, and goods and services expenditures